Oxidation of commercial (a-type) zein with hydrogen peroxide improves its hydration and dramatically increases dough extensibility even below its glass transition temperature - Taylor, J.; Johnson, Stuart; Taylor, J.; Njila, S.; Jackaman, Connie (2016)
To improve the rheological properties of zein doughs, a-type zein and zein-starch doughs were prepared with the oxidising agents, hydrogen peroxide and peroxidase, which strengthen gluten-based doughs by cross-linking. Hydrogen peroxide and peroxidase increased zein dough extensibility compared to preparation with water. Hydrogen peroxide prepared zein doughs were extensible and cohesive below zein's glass transition temperature. The doughs did not exude water and maintained flexibility when stored. Confocal laser scanning microscopy revealed that in zein-starch doughs prepared with hydrogen peroxide a thin continuous zein matrix was formed around the starch granules, whereas doughs prepared with water exhibited clumps of granules. SDS-PAGE of zein doughs and films treated with the oxidising agents showed no evidence of zein polymerisation, nor did Fourier transform infrared spectrometry reveal any significant changes in secondary structure. Further, hydrogen peroxide treatment did not increase zein film glass transition temperature, but it did increase transition enthalpy, and film water uptake increased with hydrogen peroxide concentration. The greatly increased extensibility of hydrogen peroxide prepared zein doughs and their improved water-holding are not due to oxidative cross-linking. It is proposed that the effects are primarily due to hydroxylation of amino acid aliphatic side chains, improving hydration through hydrogen bonding.